Development of a method for determining the structure of mini-grid, taking into account optimal routes of power lines in an area with sharply heterogeneous landscape - V. A. Tkachenko (Омский научный вестник)
This paper presents a method for determining the optimal structure of an isolated electrical network, taking into account the geographical features of the area in which it is located. A distinctive feature of the method is the removal of restrictions on the number of equivalent routes of power transmission lines sought, with subsequent filtering of the routes, taking into account technological and technical limitations. Thus, the obtained method can be used to organize microgrids in areas remote from the Unified National (All-Russian) Energy Grid with distributed generation and load.